"Going Public" in Comparative Perspective: Presidents' Public Appeals under Pure Presidentialism. Issue 2 (19th April 2019) - Cockerham, Alexandra G.; Driscoll, Amanda; Joseph, Joan V.
Abstract : The notion of "going public" has its origins in the U.S. presidency, yet we have little sense of how direct public appeals fit into the broader portfolio of presidential powers. We debut a new data set that includes 24 presidents from 18 countries throughout the Western Hemisphere, and show that the frequency of presidents' public appeals varies with both their partisan support in the legislature and their status as a newcomer. In so doing, we situate presidents' public appeals as an underappreciated source of executive influence in the study of comparative presidentialism.